Treatment Effects of Two Types of Fixed Functional Appliances Herbst and Korn used in Correction of Skeletal Class II Malocclusion (Journal of Hama University, 2020)
Objective: The objective of this study was to assess treatment effects on skeletal and dental changes in skeletal class II  patients after treatment with either Herbst appliance or Korn mandibular advancer as fixed functional appliances by means of lateral cephalometric radiographs.Materials and Methods of study: The sample of study consisted of (30) patients divided into two groups (G1): group one included (15) patients who were treated by Korn mandibular advancer appliance, and (G2): group two was treated by Herbst appliance.  In both groups fixed functional appliances were applied concurrently with fixed orthodontic appliance.Lateral cephalograms were taken and analyzed before treatment and after treatment. Statistical analyses were used to analyze data by ( Kolmogorov smirnov, K-S) and student's t tests. Statistical significance was set at P